Spanish pharmacies valuation: what determines their price-to-sales ratio? - Pérez, Isaac Borràs (2016)
This paper explores the relationship between the regional macroeconomic, demographic and business specific factors with the 'price-to-sales ratio' multiple used when pricing a pharmacy in Spain. Past pharmacies market studies have focused their attention on qualitative and subjective aspects in order to determine the potential value of a pharmacy. Hedonic method using multiple regression analysis shows that even when there is an expansive period the national economy, the strongest relationship performs more on regional welfare and regulation elements, behaving aligned with the traditional market perception.